Assessment and analysis of different process bus redundancy networks performance for IEC61850‐based digital substation. Issue 15 (23rd August 2018) - Xu, Luoyun; Li, Haiyu; Chen, Linwei; Patterson, Christopher; Mohapatra, Priyanka
Abstract : To achieve a highly reliable data communication network, Future Intelligent Transmission Network Substation (FITNESS) project has considered three different substation data communication redundancy networks. These include two independent parallel star networks, High‐availability Seamless Redundancy (HSR) network, and Parallel Redundancy Protocol (PRP) network. This paper presents the assessment and comparison analysis of the data flow performance for these three networks. A typical 275 kV substation with the consideration of three redundancy networks is modelled and simulated using OPNET a communication network simulation tool. The data flow capability performance with respect of the network time delay for the typical protection and control equipment requirements (e.g. IEDs and MUs) in one bay are simulated and analysed. Results show that two independent parallel star networks have the highest data flow capacity. The capacity of PRP network is reduced by a half, while the capacity of HSR network is reduced to a quarter. The results also reveal that Ethernet Switch can consume a part of network bandwidth as well. The work would help power utilities to determine an optimal number of devices to be installed and to ensure highly reliable data communication network for protection and control functions in an IEC 61850 based digital substation..